AN ASSESSMENT OF THE PENAEID PRAWN SEED RESOURCE OF THE GODAVARI ESTUARY AND THE ADJACENT BACKWATERS - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
In recent years there has been a growinginterest in prawn culture in brackishwaters.Andhra Pradesh, endowed with vastareas of backwaters and estuarine mud flats,offers an ideal environment to develop prawnculture on a commercial scale. The mostimportant input for any sort of farming is theavailability of seed near the proposed prawnfarms. Though significant breakthrough hasbeen achieved in the spawning and rearing ofpcnaeid prawns in hatcheries by the CentralMarine Fisheries Research Institute and otheragencies, large scale production of prawnseed for commercial purposes is yet to beachieved.